PRODUKSI NATA MENGGUNAKAN LIMBAH BEBERAPA JENIS KULIT PISANG - Purwanto, Agus (Widya Warta, 2012)
One way to overcome the problems of banana skin waste is to use it as raw material for the manufacture of nata through fermentation by the bacteria Acetobacter xylinum. The purpose of this experiment is to study the effect of the use of some waste of various banana skins on the physicochemical properties of nata produced. The design of experiments was conducted using Completely Randomized Design divided into four treatments, namely KP1 Â use of kepok kuning banana skin, KP2 use of raja banana skin, KP3 use ambon banana skin and KP4 use of kluthuk banana skin. Each treatment was conducted with three replications. Medium starter and fermentation made use of medium Hassids and Barker which had been modified with N sources of ZA, and vinegar table. Testing the physicochemical properties of nata produced was done through the measurements of the thickness, weight, yield, texture, and water content. The results showed that differences in the types of banana skin waste had an effect on the physicochemical properties of nata produced. The use of ambon banana skin produced the best results on the physicochemical properties of nata.